MOTIVASI MAHASISWA MENGIKUTI PROGRAM TAHFIDZ PADA PROGRAM DIRASAT AL-QUR’AN IAIN TULUNGAGUNG - Astuti, Robitoh Widi (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
There was a significant increase in the number of new students at IAINTulungagung who chose to participate at the Tahfidz program as acompulsory program that they had to carry out every Monday until Thursdaystarts from 07.00 to 08.30 am. This article outlines the motivation ofstudents to take part in the tahfidz program in the dirasat al-Qur’an IAINTulungagung program, and outlines the role of that motivation for achievingthe target of tahfidz program students in the dirasat al-Qur'an IAINTulungagung. It was concluded that the types of student motivation wereintrinsic and extrinsic. The majority of informants (83.3%) had the intrinsicmotivation and had considerable attention to memorization activities, bothunda’an and muroja’ah. The majority of informants also have a solution tothe obstacles they face in memorizing. Related to the role of motivation, themajority of informants (83.3%) have the fluctuating motivation, they(87.5%) also aware of the targets set by the Tahfidz program.